2021
DOI: 10.1186/s12889-021-11119-7
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy, health perception and related factors among different ethnic groups: a cross-sectional study in southeastern Turkey

Abstract: Background Low levels of health literacy are associated with increased hospitalization rates, problems regarding the proper intake of medications, poor general health and increased mortality rates. It is a well-known fact that health literacy differs among ethnic groups and ethnic minorities, in particular, are known to have a low level of health literacy. The present study aimed to reveal the levels of health literacy among different ethnic groups and the affecting factors as well as the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…The Q-test suggests significant heterogeneity (Q(4) = 101.12, p < 0.0001, tau2=0.03, I2 = 96.73%). One study [ 42 ] may be a potential outlier according to residually, and might be overly influential according to Cook’s distances. There was no indication for funnel plot asymmetry.…”
Section: Resultsmentioning
confidence: 99%
“…The Q-test suggests significant heterogeneity (Q(4) = 101.12, p < 0.0001, tau2=0.03, I2 = 96.73%). One study [ 42 ] may be a potential outlier according to residually, and might be overly influential according to Cook’s distances. There was no indication for funnel plot asymmetry.…”
Section: Resultsmentioning
confidence: 99%
“…was found to be adequate or excellent in health literacy [20]. Similarly, in other studies conducted in Turkey, the health literacy level of a large number of participants was evaluated as insufficient [21][22][23]. However, in a study by Özdemir in a family health center in Turkey, 51.8% of the participants reported to have a sufficient or excellent level of health literacy [24].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the status of receiving health education was determined as a factor affecting health literacy. Similarly, there are studies in the literature showing that the health education received affects the level of health literacy [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Haghdoost et al in Iran showed that 18% of the general adults population had sufficient HL, 45.7% had insufficient, and the 36.3% had moderate HL ( 3 ). In another study conducted in Turkey, 80.7% of the adults had low levels of HL ( 4 ).…”
Section: Introductionmentioning
confidence: 93%
“…High levels of HL in individuals lead to better health outcomes compared with people with low levels of HL ( 14 ). The results of a study in Iran revealed that increasing the HL led to improvements in HPBs in the health ambassadors ( 10 ), because people with higher levels of HL also have a better health perception ( 4 ). Low levels of HL result in low adherence to HPBs and a healthy lifestyle ( 15 ).…”
Section: Introductionmentioning
confidence: 99%